The Effect Of Applying Question Into Paragraph (QIP) Strategy On The Student’s Achievement In Reading Comprehension - Mahmud, Razkiah (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2023)
The objective was to investigate the effect of applying Question Into Paragraph on the students’ achievement in reading comprehension. The method of the research was the experimental research method. The population of this research was the VIII grade students of SMP Al-Washliyah 31 Medan with 60 students. The experimental group was taught by applying Question Into Paragraph ( QIP )strategy and the control was taught by applying Learning Method. The instrument of the test was Descriptive text and the students found 20 questions about the text. Based on the finding indicate that the final result was tobs ttable or 3.48 2.048 as a result showed that there was a significant effect of applying Question Into Paragraph Strategy on the students achievement in reading comprehension.